An Investigation of the Effects of Gamma Irradiation of Egg Cells on Macro and Micro Nutrients Composition of the Edible Larval Stage of Cirina forda Westwood (Lepidoptera: Saturnidae) - M. O. Odeyemi; I. K. Olayemi; A. C. Ukubuiwe; J. O. Fasoranti (Research Aspects in Biological Science Vol. 2, 2022)
The need to diversify cost-effective macro- and micronutrient enrichment of human diets has become a global priority. To this purpose, entomophagy has been promoted as a possible source of these nutrients, but it must be based on the optimization of nutritional quality of the insect candidates, which was the focus of this research. To accomplish this, freshly hatched Cirina forda eggs were treated to a variety of Gamma irradiation dosages (0, 10, 20, and 50 Gy) and then grown through the edible larval stage on the leaves of the Vitellaria paradoxa plant. The irradiation matured C. forda larvae were subjected to proximate, mineral, and micronutrient studies using standard biochemical methods. The results of proximate analysis showed that egg exposure to Gamma irradiation significantly (P<0.05) increased dry matter and carbohydrate contents, at doses of 20Gy and 50Gy, respectively (41.43±0.01 and 21.50±0.14%, respectively), the amount of crude protein, crude fibre and ash reduced slightly in the C. forda larvae, with exposure to increasing dose of gamma irradiation (from 54.82±0.12 to 50.32±0.09, 3.93±0.11 to 0.05±0.04 and 8.50±0.07 to 6.38±0.11, respectively). While the amounts of Ca and Mn reached significant peaks in larvae whose eggs were exposed to irradiation doses of 50 Gy and 10 Gy, respectively (36.03±0.01 and 8.27±0.01%), gamma irradiation significantly reduced the concentrations of Mg, K, and Fe in the insects, according to the mineral analysis. Leucine, Arginine, and Phenylalanine were the micronutrients with the greatest concentrations of 7.20±0.01, 6.86±0.01 and 5.41±0.01%, respectively, and were not substantially (p<0.05) impacted by gamma irradiation. These findings show that gamma irradiation has the potential to improve particular nutrition content in C. forda and may have a mitigating effect on anti-feedants found in the insect species, both of which require further investigation.